La Piedad de Cabadas, Michoacán, un avecindamiento de castas - Quispe Pastrana, Edgar (2025)
During the Spanish occupation of the territory of the viceroyalty of New Spain, various social nuclei were established. Thus cities, villages, forts and reductions of Indians were founded; and in other cases, ancestral villages were recognized as indigenous peoples. In the case of the current city of La Piedad de Cabadas, belonging to the state of Michoacán, Mexico, its initial process was different. Historically, it is based on two versions. One of them focuses on a discourse, without documentary support, of a Spanish foundation that would date back to 1530; The other version explains an origin from a religious perspective, linked to the miraculous appearance of a crucified Christ in 1687. However, research based on primary sources allows us to know different causes. The territory was part of the Mesoamerican P’urhépecha culture, which dominated western Mexico. Upon the arrival of the Spaniards, they allied themselves with the Iberians and the distribution of lands via Mercedes began. Since the sixteenth century, the surroundings of the future settlement were given as sites for the raising of large cattle and, at the beginning of the seventeenth century, on the banks of the Lerma River, a settlement appeared as a result of the settlement of social castes. These settlers gave rise to the original town of Aramutarillo, which later changed its name to La Piedad. At the same time as its existence, being a caste village, in official terms for political and religious administration, it was recognized as an indigenous people.